/- Copyright (c) 2014 Floris van Doorn. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Module: int.basic Authors: Floris van Doorn, Jeremy Avigad The integers, with addition, multiplication, and subtraction. The representation of the integers is chosen to compute efficiently; see the examples in the comments at the end of this file. To faciliate proving things about these operations, we show that the integers are a quotient of ℕ × ℕ with the usual equivalence relation ≡, and functions abstr : ℕ × ℕ → ℤ repr : ℤ → ℕ × ℕ satisfying abstr_repr (a : ℤ) : abstr (repr a) = a repr_abstr (p : ℕ × ℕ) : repr (abstr p) ≡ p abstr_eq (p q : ℕ × ℕ) : p ≡ q → abstr p = abstr q For example, to "lift" statements about add to statements about padd, we need to prove the following: repr_add (a b : ℤ) : repr (a + b) = padd (repr a) (repr b) padd_congr (p p' q q' : ℕ × ℕ) (H1 : p ≡ p') (H2 : q ≡ q') : padd p q ≡ p' q' -/ import data.nat.basic data.nat.order data.nat.sub data.prod import algebra.relation algebra.binary algebra.ordered_ring import tools.fake_simplifier open eq.ops open prod relation nat open decidable binary fake_simplifier /- the type of integers -/ inductive int : Type := of_nat : nat → int, neg_succ_of_nat : nat → int notation `ℤ` := int coercion [persistent] int.of_nat definition int.of_num [coercion] (n : num) : ℤ := int.of_nat (nat.of_num n) namespace int /- definitions of basic functions -/ definition neg_of_nat (m : ℕ) : ℤ := nat.cases_on m 0 (take m', neg_succ_of_nat m') definition sub_nat_nat (m n : ℕ) : ℤ := nat.cases_on (n - m) (of_nat (m - n)) -- m ≥ n (take k, neg_succ_of_nat k) -- m < n, and n - m = succ k definition neg (a : ℤ) : ℤ := cases_on a (take m, -- a = of_nat m nat.cases_on m 0 (take m', neg_succ_of_nat m')) (take m, of_nat (succ m)) -- a = neg_succ_of_nat m definition add (a b : ℤ) : ℤ := cases_on a (take m, -- a = of_nat m cases_on b (take n, of_nat (m + n)) -- b = of_nat n (take n, sub_nat_nat m (succ n))) -- b = neg_succ_of_nat n (take m, -- a = neg_succ_of_nat m cases_on b (take n, sub_nat_nat n (succ m)) -- b = of_nat n (take n, neg_of_nat (succ m + succ n))) -- b = neg_succ_of_nat n definition mul (a b : ℤ) : ℤ := cases_on a (take m, -- a = of_nat m cases_on b (take n, of_nat (m * n)) -- b = of_nat n (take n, neg_of_nat (m * succ n))) -- b = neg_succ_of_nat n (take m, -- a = neg_succ_of_nat m cases_on b (take n, neg_of_nat (succ m * n)) -- b = of_nat n (take n, of_nat (succ m * succ n))) -- b = neg_succ_of_nat n /- notation -/ notation `-[` n `+1]` := int.neg_succ_of_nat n -- for pretty-printing output prefix - := int.neg infix + := int.add infix * := int.mul /- some basic functions and properties -/ theorem of_nat_inj {m n : ℕ} (H : of_nat m = of_nat n) : m = n := no_confusion H (λe, e) theorem neg_succ_of_nat_inj {m n : ℕ} (H : neg_succ_of_nat m = neg_succ_of_nat n) : m = n := no_confusion H (λe, e) definition has_decidable_eq [instance] : decidable_eq ℤ := take a b, cases_on a (take m, cases_on b (take n, if H : m = n then inl (congr_arg of_nat H) else inr (take H1, H (of_nat_inj H1))) (take n', inr (assume H, no_confusion H))) (take m', cases_on b (take n, inr (assume H, no_confusion H)) (take n', (if H : m' = n' then inl (congr_arg neg_succ_of_nat H) else inr (take H1, H (neg_succ_of_nat_inj H1))))) theorem add_of_nat (n m : nat) : of_nat n + of_nat m = #nat n + m := rfl theorem of_nat_succ (n : ℕ) : of_nat (succ n) = of_nat n + 1 := rfl theorem mul_of_nat (n m : ℕ) : of_nat n * of_nat m = n * m := rfl theorem sub_nat_nat_of_ge {m n : ℕ} (H : m ≥ n) : sub_nat_nat m n = of_nat (m - n) := have H1 : n - m = 0, from le_imp_sub_eq_zero H, calc sub_nat_nat m n = nat.cases_on 0 (of_nat (m - n)) _ : H1 ▸ rfl ... = of_nat (m - n) : rfl theorem sub_nat_nat_of_lt {m n : ℕ} (H : m < n) : sub_nat_nat m n = neg_succ_of_nat (pred (n - m)) := have H1 : n - m = succ (pred (n - m)), from (succ_pred_of_pos (sub_pos_of_gt H))⁻¹, calc sub_nat_nat m n = nat.cases_on (succ (pred (n - m))) (of_nat (m - n)) (take k, neg_succ_of_nat k) : H1 ▸ rfl ... = neg_succ_of_nat (pred (n - m)) : rfl definition nat_abs (a : ℤ) : ℕ := cases_on a (take n, n) (take n', succ n') theorem nat_abs_of_nat (n : ℕ) : nat_abs (of_nat n) = n := rfl theorem nat_abs_eq_zero {a : ℤ} : nat_abs a = 0 → a = 0 := cases_on a (take m, assume H : nat_abs (of_nat m) = 0, congr_arg of_nat H) (take m', assume H : nat_abs (neg_succ_of_nat m') = 0, absurd H (succ_ne_zero _)) /- Show int is a quotient of ordered pairs of natural numbers, with the usual equivalence relation. -/ definition equiv (p q : ℕ × ℕ) : Prop := pr1 p + pr2 q = pr2 p + pr1 q notation [local] p `≡` q := equiv p q theorem equiv.refl {p : ℕ × ℕ} : p ≡ p := !add.comm theorem equiv.symm {p q : ℕ × ℕ} (H : p ≡ q) : q ≡ p := calc pr1 q + pr2 p = pr2 p + pr1 q : !add.comm ... = pr1 p + pr2 q : H⁻¹ ... = pr2 q + pr1 p : !add.comm theorem equiv.trans {p q r : ℕ × ℕ} (H1 : p ≡ q) (H2 : q ≡ r) : p ≡ r := have H3 : pr1 p + pr2 r + pr2 q = pr2 p + pr1 r + pr2 q, from calc pr1 p + pr2 r + pr2 q = pr1 p + pr2 q + pr2 r : by simp ... = pr2 p + pr1 q + pr2 r : {H1} ... = pr2 p + (pr1 q + pr2 r) : by simp ... = pr2 p + (pr2 q + pr1 r) : {H2} ... = pr2 p + pr1 r + pr2 q : by simp, show pr1 p + pr2 r = pr2 p + pr1 r, from add.cancel_right H3 theorem equiv_equiv : is_equivalence equiv := is_equivalence.mk @equiv.refl @equiv.symm @equiv.trans theorem equiv_cases {p q : ℕ × ℕ} (H : equiv p q) : (pr1 p ≥ pr2 p ∧ pr1 q ≥ pr2 q) ∨ (pr1 p < pr2 p ∧ pr1 q < pr2 q) := or.elim (@le_or_gt (pr2 p) (pr1 p)) (assume H1: pr1 p ≥ pr2 p, have H2 : pr2 p + pr1 q ≥ pr2 p + pr2 q, from H ▸ add_le_right H1 (pr2 q), or.inl (and.intro H1 (add_le_cancel_left H2))) (assume H1: pr1 p < pr2 p, have H2 : pr2 p + pr1 q < pr2 p + pr2 q, from H ▸ add_lt_right H1 (pr2 q), or.inr (and.intro H1 (add_lt_cancel_left H2))) theorem equiv_of_eq {p q : ℕ × ℕ} (H : p = q) : p ≡ q := H ▸ equiv.refl theorem equiv_of_eq_of_equiv {p q r : ℕ × ℕ} (H1 : p = q) (H2 : q ≡ r) : p ≡ r := H1⁻¹ ▸ H2 theorem equiv_of_equiv_of_eq {p q r : ℕ × ℕ} (H1 : p ≡ q) (H2 : q = r) : p ≡ r := H2 ▸ H1 calc_trans equiv.trans calc_refl equiv.refl calc_symm equiv.symm calc_trans equiv_of_eq_of_equiv calc_trans equiv_of_equiv_of_eq /- the representation and abstraction functions -/ definition abstr (a : ℕ × ℕ) : ℤ := sub_nat_nat (pr1 a) (pr2 a) theorem abstr_of_ge {p : ℕ × ℕ} (H : pr1 p ≥ pr2 p) : abstr p = of_nat (pr1 p - pr2 p) := sub_nat_nat_of_ge H theorem abstr_of_lt {p : ℕ × ℕ} (H : pr1 p < pr2 p) : abstr p = neg_succ_of_nat (pred (pr2 p - pr1 p)) := sub_nat_nat_of_lt H definition repr (a : ℤ) : ℕ × ℕ := cases_on a (take m, (m, 0)) (take m, (0, succ m)) theorem abstr_repr (a : ℤ) : abstr (repr a) = a := cases_on a (take m, (sub_nat_nat_of_ge (zero_le m))) (take m, rfl) theorem repr_sub_nat_nat (m n : ℕ) : repr (sub_nat_nat m n) ≡ (m, n) := or.elim (@le_or_gt n m) (take H : m ≥ n, have H1 : repr (sub_nat_nat m n) = (m - n, 0), from sub_nat_nat_of_ge H ▸ rfl, H1⁻¹ ▸ (calc m - n + n = m : add_sub_ge_left H ... = 0 + m : add.zero_left)) (take H : m < n, have H1 : repr (sub_nat_nat m n) = (0, succ (pred (n - m))), from sub_nat_nat_of_lt H ▸ rfl, H1⁻¹ ▸ (calc 0 + n = n : add.zero_left ... = n - m + m : add_sub_ge_left (lt_imp_le H) ... = succ (pred (n - m)) + m : (succ_pred_of_pos (sub_pos_of_gt H))⁻¹)) theorem repr_abstr (p : ℕ × ℕ) : repr (abstr p) ≡ p := !prod.eta ▸ !repr_sub_nat_nat theorem abstr_eq {p q : ℕ × ℕ} (Hequiv : p ≡ q) : abstr p = abstr q := or.elim (equiv_cases Hequiv) (assume H2, have H3 : pr1 p ≥ pr2 p, from and.elim_left H2, have H4 : pr1 q ≥ pr2 q, from and.elim_right H2, have H5 : pr1 p = pr1 q - pr2 q + pr2 p, from calc pr1 p = pr1 p + pr2 q - pr2 q : sub_add_left ... = pr2 p + pr1 q - pr2 q : Hequiv ... = pr2 p + (pr1 q - pr2 q) : add_sub_assoc H4 ... = pr1 q - pr2 q + pr2 p : add.comm, have H6 : pr1 p - pr2 p = pr1 q - pr2 q, from calc pr1 p - pr2 p = pr1 q - pr2 q + pr2 p - pr2 p : H5 ... = pr1 q - pr2 q : sub_add_left, abstr_of_ge H3 ⬝ congr_arg of_nat H6 ⬝ (abstr_of_ge H4)⁻¹) (assume H2, have H3 : pr1 p < pr2 p, from and.elim_left H2, have H4 : pr1 q < pr2 q, from and.elim_right H2, have H5 : pr2 p = pr2 q - pr1 q + pr1 p, from calc pr2 p = pr2 p + pr1 q - pr1 q : sub_add_left ... = pr1 p + pr2 q - pr1 q : Hequiv ... = pr1 p + (pr2 q - pr1 q) : add_sub_assoc (lt_imp_le H4) ... = pr2 q - pr1 q + pr1 p : add.comm, have H6 : pr2 p - pr1 p = pr2 q - pr1 q, from calc pr2 p - pr1 p = pr2 q - pr1 q + pr1 p - pr1 p : H5 ... = pr2 q - pr1 q : sub_add_left, abstr_of_lt H3 ⬝ congr_arg neg_succ_of_nat (congr_arg pred H6)⬝ (abstr_of_lt H4)⁻¹) theorem equiv_iff (p q : ℕ × ℕ) : (p ≡ q) ↔ ((p ≡ p) ∧ (q ≡ q) ∧ (abstr p = abstr q)) := iff.intro (assume H : equiv p q, and.intro !equiv.refl (and.intro !equiv.refl (abstr_eq H))) (assume H : equiv p p ∧ equiv q q ∧ abstr p = abstr q, have H1 : abstr p = abstr q, from and.elim_right (and.elim_right H), equiv.trans (H1 ▸ equiv.symm (repr_abstr p)) (repr_abstr q)) theorem eq_abstr_of_equiv_repr {a : ℤ} {p : ℕ × ℕ} (Hequiv : repr a ≡ p) : a = abstr p := calc a = abstr (repr a) : abstr_repr ... = abstr p : abstr_eq Hequiv theorem eq_of_repr_equiv_repr {a b : ℤ} (H : repr a ≡ repr b) : a = b := calc a = abstr (repr a) : abstr_repr ... = abstr (repr b) : abstr_eq H ... = b : abstr_repr theorem nat_abs_abstr (p : ℕ × ℕ) : nat_abs (abstr p) = dist (pr1 p) (pr2 p) := let m := pr1 p, n := pr2 p in or.elim (@le_or_gt n m) (assume H : m ≥ n, calc nat_abs (abstr (m, n)) = nat_abs (of_nat (m - n)) : int.abstr_of_ge H ... = dist m n : dist_ge H) (assume H : m < n, calc nat_abs (abstr (m, n)) = nat_abs (neg_succ_of_nat (pred (n - m))) : int.abstr_of_lt H ... = succ (pred (n - m)) : rfl ... = n - m : succ_pred_of_pos (sub_pos_of_gt H) ... = dist m n : dist_le (lt_imp_le H)) theorem cases_of_nat (a : ℤ) : (∃n : ℕ, a = of_nat n) ∨ (∃n : ℕ, a = - of_nat n) := cases_on a (take n, or.inl (exists.intro n rfl)) (take n', or.inr (exists.intro (succ n') rfl)) theorem cases_of_nat_succ (a : ℤ) : (∃n : ℕ, a = of_nat n) ∨ (∃n : ℕ, a = - (of_nat (succ n))) := int.cases_on a (take m, or.inl (exists.intro _ rfl)) (take m, or.inr (exists.intro _ rfl)) theorem by_cases_of_nat {P : ℤ → Prop} (a : ℤ) (H1 : ∀n : ℕ, P (of_nat n)) (H2 : ∀n : ℕ, P (- of_nat n)) : P a := or.elim (cases_of_nat a) (assume H, obtain (n : ℕ) (H3 : a = n), from H, H3⁻¹ ▸ H1 n) (assume H, obtain (n : ℕ) (H3 : a = -n), from H, H3⁻¹ ▸ H2 n) theorem by_cases_of_nat_succ {P : ℤ → Prop} (a : ℤ) (H1 : ∀n : ℕ, P (of_nat n)) (H2 : ∀n : ℕ, P (- of_nat (succ n))) : P a := or.elim (cases_of_nat_succ a) (assume H, obtain (n : ℕ) (H3 : a = n), from H, H3⁻¹ ▸ H1 n) (assume H, obtain (n : ℕ) (H3 : a = -(succ n)), from H, H3⁻¹ ▸ H2 n) /- Show int is a ring. -/ /- addition -/ definition padd (p q : ℕ × ℕ) : ℕ × ℕ := map_pair2 nat.add p q theorem repr_add (a b : ℤ) : repr (add a b) ≡ padd (repr a) (repr b) := cases_on a (take m, cases_on b (take n, !equiv.refl) (take n', have H1 : equiv (repr (add (of_nat m) (neg_succ_of_nat n'))) (m, succ n'), from !repr_sub_nat_nat, have H2 : padd (repr (of_nat m)) (repr (neg_succ_of_nat n')) = (m, 0 + succ n'), from rfl, (!add.zero_left ▸ H2)⁻¹ ▸ H1)) (take m', cases_on b (take n, have H1 : equiv (repr (add (neg_succ_of_nat m') (of_nat n))) (n, succ m'), from !repr_sub_nat_nat, have H2 : padd (repr (neg_succ_of_nat m')) (repr (of_nat n)) = (0 + n, succ m'), from rfl, (!add.zero_left ▸ H2)⁻¹ ▸ H1) (take n',!repr_sub_nat_nat)) theorem padd_congr {p p' q q' : ℕ × ℕ} (Ha : p ≡ p') (Hb : q ≡ q') : padd p q ≡ padd p' q' := calc pr1 (padd p q) + pr2 (padd p' q') = pr1 p + pr2 p' + (pr1 q + pr2 q') : by simp ... = pr2 p + pr1 p' + (pr1 q + pr2 q') : {Ha} ... = pr2 p + pr1 p' + (pr2 q + pr1 q') : {Hb} ... = pr2 (padd p q) + pr1 (padd p' q') : by simp theorem padd_comm (p q : ℕ × ℕ) : padd p q = padd q p := calc padd p q = (pr1 p + pr1 q, pr2 p + pr2 q) : rfl ... = (pr1 q + pr1 p, pr2 p + pr2 q) : add.comm ... = (pr1 q + pr1 p, pr2 q + pr2 p) : add.comm ... = padd q p : rfl theorem padd_assoc (p q r : ℕ × ℕ) : padd (padd p q) r = padd p (padd q r) := calc padd (padd p q) r = (pr1 p + pr1 q + pr1 r, pr2 p + pr2 q + pr2 r) : rfl ... = (pr1 p + (pr1 q + pr1 r), pr2 p + pr2 q + pr2 r) : add.assoc ... = (pr1 p + (pr1 q + pr1 r), pr2 p + (pr2 q + pr2 r)) : add.assoc ... = padd p (padd q r) : rfl theorem add.comm (a b : ℤ) : a + b = b + a := begin apply eq_of_repr_equiv_repr, apply equiv.trans, apply repr_add, apply equiv.symm, apply (eq.subst (padd_comm (repr b) (repr a))), apply repr_add end theorem add.assoc (a b c : ℤ) : a + b + c = a + (b + c) := have H1 [visible]: repr (a + b + c) ≡ padd (padd (repr a) (repr b)) (repr c), from equiv.trans (repr_add (a + b) c) (padd_congr !repr_add !equiv.refl), have H2 [visible]: repr (a + (b + c)) ≡ padd (repr a) (padd (repr b) (repr c)), from equiv.trans (repr_add a (b + c)) (padd_congr !equiv.refl !repr_add), begin apply eq_of_repr_equiv_repr, apply equiv.trans, apply H1, apply (eq.subst ((padd_assoc _ _ _)⁻¹)), apply equiv.symm, apply H2 end theorem add.right_id (a : ℤ) : a + 0 = a := cases_on a (take m, rfl) (take m', rfl) theorem add.left_id (a : ℤ) : 0 + a = a := add.comm a 0 ▸ add.right_id a /- negation -/ definition pneg (p : ℕ × ℕ) : ℕ × ℕ := (pr2 p, pr1 p) -- note: this is =, not just ≡ theorem repr_neg (a : ℤ) : repr (- a) = pneg (repr a) := cases_on a (take m, nat.cases_on m rfl (take m', rfl)) (take m', rfl) theorem pneg_congr {p p' : ℕ × ℕ} (H : p ≡ p') : pneg p ≡ pneg p' := eq.symm H theorem pneg_pneg (p : ℕ × ℕ) : pneg (pneg p) = p := !prod.eta theorem nat_abs_neg (a : ℤ) : nat_abs (-a) = nat_abs a := calc nat_abs (-a) = nat_abs (abstr (repr (-a))) : abstr_repr ... = nat_abs (abstr (pneg (repr a))) : repr_neg ... = dist (pr1 (pneg (repr a))) (pr2 (pneg (repr a))) : nat_abs_abstr ... = dist (pr2 (pneg (repr a))) (pr1 (pneg (repr a))) : dist_comm ... = nat_abs (abstr (repr a)) : nat_abs_abstr ... = nat_abs a : abstr_repr theorem padd_pneg (p : ℕ × ℕ) : padd p (pneg p) ≡ (0, 0) := show pr1 p + pr2 p + 0 = pr2 p + pr1 p + 0, from !nat.add.comm ▸ rfl theorem padd_padd_pneg (p q : ℕ × ℕ) : padd (padd p q) (pneg q) ≡ p := show pr1 p + pr1 q + pr2 q + pr2 p = pr2 p + pr2 q + pr1 q + pr1 p, by simp theorem add.left_inv (a : ℤ) : -a + a = 0 := have H : repr (-a + a) ≡ repr 0, from calc repr (-a + a) ≡ padd (repr (neg a)) (repr a) : repr_add ... = padd (pneg (repr a)) (repr a) : repr_neg ... ≡ repr 0 : padd_pneg, eq_of_repr_equiv_repr H /- nat -/ definition pabs (p : ℕ × ℕ) : ℕ := dist (pr1 p) (pr2 p) theorem pabs_congr {p q : ℕ × ℕ} (H : p ≡ q) : pabs p = pabs q := calc pabs p = nat_abs (abstr p) : nat_abs_abstr ... = nat_abs (abstr q) : abstr_eq H ... = pabs q : nat_abs_abstr theorem nat_abs_eq_pabs_repr (a : ℤ) : nat_abs a = pabs (repr a) := calc nat_abs a = nat_abs (abstr (repr a)) : abstr_repr ... = pabs (repr a) : nat_abs_abstr theorem nat_abs_add_le (a b : ℤ) : nat_abs (a + b) ≤ nat_abs a + nat_abs b := have H : nat_abs (a + b) = pabs (padd (repr a) (repr b)), from calc nat_abs (a + b) = pabs (repr (a + b)) : nat_abs_eq_pabs_repr ... = pabs (padd (repr a) (repr b)) : pabs_congr !repr_add, have H1 : nat_abs a = pabs (repr a), from !nat_abs_eq_pabs_repr, have H2 : nat_abs b = pabs (repr b), from !nat_abs_eq_pabs_repr, have H3 : pabs (padd (repr a) (repr b)) ≤ pabs (repr a) + pabs (repr b), from !dist_add_le_add_dist, H⁻¹ ▸ H1⁻¹ ▸ H2⁻¹ ▸ H3 theorem mul_nat_abs (a b : ℤ) : nat_abs (a * b) = #nat (nat_abs a) * (nat_abs b) := cases_on a (take m, cases_on b (take n, rfl) (take n', !nat_abs_neg ▸ rfl)) (take m', cases_on b (take n, !nat_abs_neg ▸ rfl) (take n', rfl)) /- multiplication -/ definition pmul (p q : ℕ × ℕ) : ℕ × ℕ := (pr1 p * pr1 q + pr2 p * pr2 q, pr1 p * pr2 q + pr2 p * pr1 q) theorem repr_neg_of_nat (m : ℕ) : repr (neg_of_nat m) = (0, m) := nat.cases_on m rfl (take m', rfl) -- note: we have =, not just ≡ theorem repr_mul (a b : ℤ) : repr (mul a b) = pmul (repr a) (repr b) := cases_on a (take m, cases_on b (take n, (calc pmul (repr m) (repr n) = (m * n + 0 * 0, m * 0 + 0 * n) : rfl ... = (m * n + 0 * 0, m * 0 + 0) : mul.zero_left)⁻¹) (take n', (calc pmul (repr m) (repr (neg_succ_of_nat n')) = (m * 0 + 0 * succ n', m * succ n' + 0 * 0) : rfl ... = (m * 0 + 0, m * succ n' + 0 * 0) : mul.zero_left ... = repr (mul m (neg_succ_of_nat n')) : repr_neg_of_nat)⁻¹)) (take m', cases_on b (take n, (calc pmul (repr (neg_succ_of_nat m')) (repr n) = (0 * n + succ m' * 0, 0 * 0 + succ m' * n) : rfl ... = (0 + succ m' * 0, 0 * 0 + succ m' * n) : mul.zero_left ... = (0 + succ m' * 0, succ m' * n) : add.zero_left ... = repr (mul (neg_succ_of_nat m') n) : repr_neg_of_nat)⁻¹) (take n', (calc pmul (repr (neg_succ_of_nat m')) (repr (neg_succ_of_nat n')) = (0 + succ m' * succ n', 0 * succ n') : rfl ... = (succ m' * succ n', 0 * succ n') : add.zero_left ... = (succ m' * succ n', 0) : mul.zero_left ... = repr (mul (neg_succ_of_nat m') (neg_succ_of_nat n')) : rfl)⁻¹)) theorem equiv_mul_prep {xa ya xb yb xn yn xm ym : ℕ} (H1 : xa + yb = ya + xb) (H2 : xn + ym = yn + xm) : xa * xn + ya * yn + (xb * ym + yb * xm) = xa * yn + ya * xn + (xb * xm + yb * ym) := have H3 : xa * xn + ya * yn + (xb * ym + yb * xm) + (yb * xn + xb * yn + (xb * xn + yb * yn)) = xa * yn + ya * xn + (xb * xm + yb * ym) + (yb * xn + xb * yn + (xb * xn + yb * yn)), from calc xa * xn + ya * yn + (xb * ym + yb * xm) + (yb * xn + xb * yn + (xb * xn + yb * yn)) = xa * xn + yb * xn + (ya * yn + xb * yn) + (xb * xn + xb * ym + (yb * yn + yb * xm)) : by simp ... = (xa + yb) * xn + (ya + xb) * yn + (xb * (xn + ym) + yb * (yn + xm)) : by simp ... = (ya + xb) * xn + (xa + yb) * yn + (xb * (yn + xm) + yb * (xn + ym)) : by simp ... = ya * xn + xb * xn + (xa * yn + yb * yn) + (xb * yn + xb * xm + (yb*xn + yb*ym)) : by simp ... = xa * yn + ya * xn + (xb * xm + yb * ym) + (yb * xn + xb * yn + (xb * xn + yb * yn)) : by simp, nat.add.cancel_right H3 theorem pmul_congr {p p' q q' : ℕ × ℕ} (H1 : p ≡ p') (H2 : q ≡ q') : pmul p q ≡ pmul p' q' := equiv_mul_prep H1 H2 theorem pmul_comm (p q : ℕ × ℕ) : pmul p q = pmul q p := calc (pr1 p * pr1 q + pr2 p * pr2 q, pr1 p * pr2 q + pr2 p * pr1 q) = (pr1 q * pr1 p + pr2 p * pr2 q, pr1 p * pr2 q + pr2 p * pr1 q) : mul.comm ... = (pr1 q * pr1 p + pr2 q * pr2 p, pr1 p * pr2 q + pr2 p * pr1 q) : mul.comm ... = (pr1 q * pr1 p + pr2 q * pr2 p, pr2 q * pr1 p + pr2 p * pr1 q) : mul.comm ... = (pr1 q * pr1 p + pr2 q * pr2 p, pr2 q * pr1 p + pr1 q * pr2 p) : mul.comm ... = (pr1 q * pr1 p + pr2 q * pr2 p, pr1 q * pr2 p + pr2 q * pr1 p) : nat.add.comm theorem mul.comm (a b : ℤ) : a * b = b * a := eq_of_repr_equiv_repr ((calc repr (a * b) = pmul (repr a) (repr b) : repr_mul ... = pmul (repr b) (repr a) : pmul_comm ... = repr (b * a) : repr_mul) ▸ !equiv.refl) theorem pmul_assoc (p q r: ℕ × ℕ) : pmul (pmul p q) r = pmul p (pmul q r) := by simp theorem mul.assoc (a b c : ℤ) : (a * b) * c = a * (b * c) := eq_of_repr_equiv_repr ((calc repr (a * b * c) = pmul (repr (a * b)) (repr c) : repr_mul ... = pmul (pmul (repr a) (repr b)) (repr c) : repr_mul ... = pmul (repr a) (pmul (repr b) (repr c)) : pmul_assoc ... = pmul (repr a) (repr (b * c)) : repr_mul ... = repr (a * (b * c)) : repr_mul) ▸ !equiv.refl) theorem mul.right_id (a : ℤ) : a * 1 = a := eq_of_repr_equiv_repr (equiv_of_eq ((calc repr (a * 1) = pmul (repr a) (repr 1) : repr_mul ... = (pr1 (repr a), pr2 (repr a)) : by simp ... = repr a : prod.eta))) theorem mul.left_id (a : ℤ) : 1 * a = a := mul.comm a 1 ▸ mul.right_id a theorem mul.right_distrib (a b c : ℤ) : (a + b) * c = a * c + b * c := eq_of_repr_equiv_repr (calc repr ((a + b) * c) = pmul (repr (a + b)) (repr c) : repr_mul ... ≡ pmul (padd (repr a) (repr b)) (repr c) : pmul_congr !repr_add equiv.refl ... = padd (pmul (repr a) (repr c)) (pmul (repr b) (repr c)) : by simp ... = padd (repr (a * c)) (pmul (repr b) (repr c)) : {(repr_mul a c)⁻¹} ... = padd (repr (a * c)) (repr (b * c)) : repr_mul ... ≡ repr (a * c + b * c) : equiv.symm !repr_add) theorem mul.left_distrib (a b c : ℤ) : a * (b + c) = a * b + a * c := calc a * (b + c) = (b + c) * a : mul.comm a (b + c) ... = b * a + c * a : mul.right_distrib b c a ... = a * b + c * a : {mul.comm b a} ... = a * b + a * c : {mul.comm c a} theorem zero_ne_one : (typeof 0 : int) ≠ 1 := assume H : 0 = 1, show false, from succ_ne_zero 0 ((of_nat_inj H)⁻¹) theorem eq_zero_or_eq_zero_of_mul_eq_zero {a b : ℤ} (H : a * b = 0) : a = 0 ∨ b = 0 := have H2 : (nat_abs a) * (nat_abs b) = nat.zero, from calc (nat_abs a) * (nat_abs b) = (nat_abs (a * b)) : (mul_nat_abs a b)⁻¹ ... = (nat_abs 0) : {H} ... = nat.zero : nat_abs_of_nat nat.zero, have H3 : (nat_abs a) = nat.zero ∨ (nat_abs b) = nat.zero, from mul.eq_zero H2, or_of_or_of_imp_of_imp H3 (assume H : (nat_abs a) = nat.zero, nat_abs_eq_zero H) (assume H : (nat_abs b) = nat.zero, nat_abs_eq_zero H) definition integral_domain : algebra.integral_domain int := algebra.integral_domain.mk add add.assoc zero add.left_id add.right_id neg add.left_inv add.comm mul mul.assoc (of_num 1) mul.left_id mul.right_id mul.left_distrib mul.right_distrib zero_ne_one mul.comm @eq_zero_or_eq_zero_of_mul_eq_zero /- Instantiate ring theorems to int -/ -- TODO: make this "section" when scoping bug is fixed context port_algebra open algebra instance integral_domain theorem mul.left_comm : ∀a b c : ℤ, a * (b * c) = b * (a * c) := algebra.mul.left_comm theorem mul.right_comm : ∀a b c : ℤ, (a * b) * c = (a * c) * b := algebra.mul.right_comm theorem add.left_comm : ∀a b c : ℤ, a + (b + c) = b + (a + c) := algebra.add.left_comm theorem add.right_comm : ∀a b c : ℤ, (a + b) + c = (a + c) + b := algebra.add.right_comm theorem add.left_cancel : ∀{a b c : ℤ}, a + b = a + c → b = c := @algebra.add.left_cancel _ _ theorem add.right_cancel : ∀{a b c : ℤ}, a + b = c + b → a = c := @algebra.add.right_cancel _ _ theorem neg_add_cancel_left : ∀a b : ℤ, -a + (a + b) = b := algebra.neg_add_cancel_left theorem neg_add_cancel_right : ∀a b : ℤ, a + -b + b = a := algebra.neg_add_cancel_right theorem neg_eq_of_add_eq_zero : ∀{a b : ℤ}, a + b = 0 → -a = b := @algebra.neg_eq_of_add_eq_zero _ _ theorem neg_zero : -0 = 0 := algebra.neg_zero theorem neg_neg : ∀a : ℤ, -(-a) = a := algebra.neg_neg theorem neg.inj : ∀{a b : ℤ}, -a = -b → a = b := @algebra.neg.inj _ _ theorem neg_eq_neg_iff_eq : ∀a b : ℤ, -a = -b ↔ a = b := algebra.neg_eq_neg_iff_eq theorem neg_eq_zero_iff_eq_zero : ∀a : ℤ, -a = 0 ↔ a = 0 := algebra.neg_eq_zero_iff_eq_zero theorem eq_neg_of_eq_neg : ∀{a b : ℤ}, a = -b → b = -a := @algebra.eq_neg_of_eq_neg _ _ theorem eq_neg_iff_eq_neg : ∀{a b : ℤ}, a = -b ↔ b = -a := @algebra.eq_neg_iff_eq_neg _ _ theorem add.right_inv : ∀a : ℤ, a + -a = 0 := algebra.add.right_inv theorem add_neg_cancel_left : ∀a b : ℤ, a + (-a + b) = b := algebra.add_neg_cancel_left theorem add_neg_cancel_right : ∀a b : ℤ, a + b + -b = a := algebra.add_neg_cancel_right theorem neg_add_eq : ∀a b : ℤ, -(a + b) = -b + -a := algebra.neg_add_eq theorem eq_add_neg_of_add_eq : ∀{a b c : ℤ}, a + b = c → a = c + -b := @algebra.eq_add_neg_of_add_eq _ _ theorem eq_neg_add_of_add_eq : ∀{a b c : ℤ}, a + b = c → b = -a + c := @algebra.eq_neg_add_of_add_eq _ _ theorem neg_add_eq_of_eq_add : ∀{a b c : ℤ}, a = b + c → -b + a = c := @algebra.neg_add_eq_of_eq_add _ _ theorem add_neg_eq_of_eq_add : ∀{a b c : ℤ}, a = b + c → a + -c = b := @algebra.add_neg_eq_of_eq_add _ _ theorem eq_add_of_add_neg_eq : ∀{a b c : ℤ}, a + -b = c → a = c + b := @algebra.eq_add_of_add_neg_eq _ _ theorem eq_add_of_neg_add_eq : ∀{a b c : ℤ}, -a + b = c → b = a + c := @algebra.eq_add_of_neg_add_eq _ _ theorem add_eq_of_eq_neg_add : ∀{a b c : ℤ}, a = -b + c → b + a = c := @algebra.add_eq_of_eq_neg_add _ _ theorem add_eq_of_eq_add_neg : ∀{a b c : ℤ}, a = b + -c → a + c = b := @algebra.add_eq_of_eq_add_neg _ _ theorem add_eq_iff_eq_neg_add : ∀a b c : ℤ, a + b = c ↔ b = -a + c := @algebra.add_eq_iff_eq_neg_add _ _ theorem add_eq_iff_eq_add_neg : ∀a b c : ℤ, a + b = c ↔ a = c + -b := @algebra.add_eq_iff_eq_add_neg _ _ definition sub (a b : ℤ) : ℤ := algebra.sub a b infix - := int.sub theorem sub_self : ∀a : ℤ, a - a = 0 := algebra.sub_self theorem sub_add_cancel : ∀a b : ℤ, a - b + b = a := algebra.sub_add_cancel theorem add_sub_cancel : ∀a b : ℤ, a + b - b = a := algebra.add_sub_cancel theorem eq_of_sub_eq_zero : ∀{a b : ℤ}, a - b = 0 → a = b := @algebra.eq_of_sub_eq_zero _ _ theorem eq_iff_sub_eq_zero : ∀a b : ℤ, a = b ↔ a - b = 0 := algebra.eq_iff_sub_eq_zero theorem zero_sub_eq : ∀a : ℤ, 0 - a = -a := algebra.zero_sub_eq theorem sub_zero_eq : ∀a : ℤ, a - 0 = a := algebra.sub_zero_eq theorem sub_neg_eq_add : ∀a b : ℤ, a - (-b) = a + b := algebra.sub_neg_eq_add theorem neg_sub_eq : ∀a b : ℤ, -(a - b) = b - a := algebra.neg_sub_eq theorem add_sub_eq : ∀a b c : ℤ, a + (b - c) = a + b - c := algebra.add_sub_eq theorem sub_add_eq_sub_sub_swap : ∀a b c : ℤ, a - (b + c) = a - c - b := algebra.sub_add_eq_sub_sub_swap theorem sub_eq_iff_eq_add : ∀a b c : ℤ, a - b = c ↔ a = c + b := algebra.sub_eq_iff_eq_add theorem eq_sub_iff_add_eq : ∀a b c : ℤ, a = b - c ↔ a + c = b := algebra.eq_sub_iff_add_eq theorem eq_iff_eq_of_sub_eq_sub : ∀{a b c d : ℤ}, a - b = c - d → a = b ↔ c = d := @algebra.eq_iff_eq_of_sub_eq_sub _ _ theorem sub_add_eq_sub_sub : ∀a b c : ℤ, a - (b + c) = a - b - c := algebra.sub_add_eq_sub_sub theorem neg_add_eq_sub : ∀a b : ℤ, -a + b = b - a := algebra.neg_add_eq_sub theorem neg_add_distrib : ∀a b : ℤ, -(a + b) = -a + -b := algebra.neg_add_distrib theorem sub_add_eq_add_sub : ∀a b c : ℤ, a - b + c = a + c - b := algebra.sub_add_eq_add_sub theorem sub_sub_eq : ∀a b c : ℤ, a - b - c = a - (b + c) := algebra.sub_sub_eq theorem add_sub_add_left_eq_sub : ∀a b c : ℤ, (c + a) - (c + b) = a - b := algebra.add_sub_add_left_eq_sub theorem ne_zero_of_mul_ne_zero_right : ∀{a b : ℤ}, a * b ≠ 0 → a ≠ 0 := @algebra.ne_zero_of_mul_ne_zero_right _ _ theorem ne_zero_of_mul_ne_zero_left : ∀{a b : ℤ}, a * b ≠ 0 → b ≠ 0 := @algebra.ne_zero_of_mul_ne_zero_left _ _ definition dvd (a b : ℤ) : Prop := algebra.dvd a b infix `|` := dvd theorem dvd.intro : ∀{a b c : ℤ} (H : a * b = c), a | c := @algebra.dvd.intro _ _ theorem dvd.ex : ∀{a b : ℤ} (H : a | b), ∃c, a * c = b := @algebra.dvd.ex _ _ theorem dvd.elim : ∀{P : Prop} {a b : ℤ} (H₁ : a | b) (H₂ : ∀c, a * c = b → P), P := @algebra.dvd.elim _ _ theorem dvd.refl : ∀a : ℤ, a | a := algebra.dvd.refl theorem dvd.trans : ∀{a b c : ℤ} (H₁ : a | b) (H₂ : b | c), a | c := @algebra.dvd.trans _ _ theorem eq_zero_of_zero_dvd : ∀(a : ℤ) {H : 0 | a}, a = 0 := @algebra.eq_zero_of_zero_dvd _ _ theorem dvd_zero : ∀a : ℤ, a | 0 := algebra.dvd_zero theorem one_dvd : ∀a : ℤ, 1 | a := algebra.one_dvd theorem dvd_mul_right : ∀a b : ℤ, a | a * b := algebra.dvd_mul_right theorem dvd_mul_left : ∀a b : ℤ, a | b * a := algebra.dvd_mul_left theorem dvd_mul_of_dvd_left : ∀{a b : ℤ} (H : a | b) (c : ℤ), a | b * c := @algebra.dvd_mul_of_dvd_left _ _ theorem dvd_mul_of_dvd_right : ∀{a b : ℤ} (H : a | b) (c : ℤ), a | c * b := @algebra.dvd_mul_of_dvd_right _ _ theorem mul_dvd_mul : ∀{a b c d : ℤ}, a | b → c | d → a * c | b * d := @algebra.mul_dvd_mul _ _ theorem dvd_of_mul_right_dvd : ∀{a b c : ℤ}, a * b | c → a | c := @algebra.dvd_of_mul_right_dvd _ _ theorem dvd_of_mul_left_dvd : ∀{a b c : ℤ}, a * b | c → b | c := @algebra.dvd_of_mul_left_dvd _ _ theorem dvd_add : ∀{a b c : ℤ}, a | b → a | c → a | b + c := @algebra.dvd_add _ _ theorem zero_mul_eq : ∀a : ℤ, 0 * a = 0 := algebra.zero_mul_eq theorem mul_zero_eq : ∀a : ℤ, a * 0 = 0 := algebra.mul_zero_eq theorem neg_mul_eq_neg_mul : ∀a b : ℤ, -(a * b) = -a * b := algebra.neg_mul_eq_neg_mul theorem neg_mul_eq_mul_neg : ∀a b : ℤ, -(a * b) = a * -b := algebra.neg_mul_eq_mul_neg theorem neg_mul_neg_eq : ∀a b : ℤ, -a * -b = a * b := algebra.neg_mul_neg_eq theorem neg_mul_comm : ∀a b : ℤ, -a * b = a * -b := algebra.neg_mul_comm theorem mul_sub_left_distrib : ∀a b c : ℤ, a * (b - c) = a * b - a * c := algebra.mul_sub_left_distrib theorem mul_sub_right_distrib : ∀a b c : ℤ, (a - b) * c = a * c - b * c := algebra.mul_sub_right_distrib theorem mul_add_eq_mul_add_iff_sub_mul_add_eq : ∀a b c d e : ℤ, a * e + c = b * e + d ↔ (a - b) * e + c = d := algebra.mul_add_eq_mul_add_iff_sub_mul_add_eq theorem mul_self_sub_mul_self_eq : ∀a b : ℤ, a * a - b * b = (a + b) * (a - b) := algebra.mul_self_sub_mul_self_eq theorem mul_self_sub_one_eq : ∀a : ℤ, a * a - 1 = (a + 1) * (a - 1) := algebra.mul_self_sub_one_eq theorem dvd_neg_iff_dvd : ∀a b : ℤ, a | -b ↔ a | b := algebra.dvd_neg_iff_dvd theorem neg_dvd_iff_dvd : ∀a b : ℤ, -a | b ↔ a | b := algebra.neg_dvd_iff_dvd theorem dvd_sub : ∀a b c : ℤ, a | b → a | c → a | (b - c) := algebra.dvd_sub theorem mul_ne_zero : ∀{a b : ℤ}, a ≠ 0 → b ≠ 0 → a * b ≠ 0 := @algebra.mul_ne_zero _ _ theorem mul.cancel_right : ∀{a b c : ℤ}, a ≠ 0 → b * a = c * a → b = c := @algebra.mul.cancel_right _ _ theorem mul.cancel_left : ∀{a b c : ℤ}, a ≠ 0 → a * b = a * c → b = c := @algebra.mul.cancel_left _ _ theorem mul_self_eq_mul_self_iff : ∀a b : ℤ, a * a = b * b ↔ a = b ∨ a = -b := algebra.mul_self_eq_mul_self_iff theorem mul_self_eq_one_iff : ∀a : ℤ, a * a = 1 ↔ a = 1 ∨ a = -1 := algebra.mul_self_eq_one_iff theorem dvd_of_mul_dvd_mul_left : ∀{a b c : ℤ}, a ≠ 0 → a * b | a * c → b | c := @algebra.dvd_of_mul_dvd_mul_left _ _ theorem dvd_of_mul_dvd_mul_right : ∀{a b c : ℤ}, a ≠ 0 → b * a | c * a → b | c := @algebra.dvd_of_mul_dvd_mul_right _ _ end port_algebra -- TODO: declare appropriate rewrite rules -- add_rewrite add_left_id add_right_id -- add_rewrite add_comm add.assoc add_left_comm -- add_rewrite sub_def add_inverse_right add_inverse_left -- add_rewrite neg_add_distr ---- add_rewrite sub_sub_assoc sub_add_assoc add_sub_assoc ---- add_rewrite add_neg_right add_neg_left ---- add_rewrite sub_self end int /- tests -/ /- open int eval -100 eval -(-100) eval #int (5 + 7) eval -5 + 7 eval 5 + -7 eval -5 + -7 eval #int 155 + 277 eval -155 + 277 eval 155 + -277 eval -155 + -277 eval #int 155 - 277 eval #int 277 - 155 eval #int 2 * 3 eval -2 * 3 eval 2 * -3 eval -2 * -3 eval 22 * 33 eval -22 * 33 eval 22 * -33 eval -22 * -33 eval #int 22 ≤ 33 eval #int 33 ≤ 22 example : #int 22 ≤ 33 := true.intro example : #int -5 < 7 := true.intro -/